RESEARCH OF THE PROPERTIES OF RAW MATERIALS AND YARN FROM COTTON FIBERS COLLECTED BY DIFFERENT METHODS - Paluanov Bakhtiyar Aralbaevich; Aliev Azizbek Raxmanbergen ugli (European Journal of Interdisciplinary Research and Development, 2024)
The article presents the results of experiments conducted to study the quality indicators of machine- and hand-picked cotton fiber, semi-finished products and yarn.